Encouraging Teacher Innovation: The Role of Organizational Support, Self-Management, and Trust as reviewed from SITOREM analysis - Gresinta, Efri; Setyaningsih, Sri; Novita, Lina (JURNAL AL-TANZIM, 2026)
This study aims to analyze the influence of organizational support, self-management, and trust on innovation in vocational high school (SMK) teachers. This study employed a mixed methods approach with a sequential explanatory design. The qualitative phase involved structured interviews to explore teachers’ perceptions and practices, followed by a quantitative phase through a survey of private vocational high school teachers. Data analysis was conducted using the POP-SDM (Modeling and Optimization of Strengthening Management Resources) approach combined with SITOREM analysis. The results indicate that organizational support, self-management, and trust have a positive and significant effect on teacher innovation. Furthermore, SITOREM analysis identified priority indicators that need immediate improvement: compliance with regulations, interpersonal trust, independence, self-development, and the ability to implement and develop ideas. The implications of this study emphasize the importance of strengthening school policies that support leadership, improving teacher self-management, and building a climate of trust to encourage sustainable teacher innovation in addressing the challenges of educational transformation.